2018
DOI: 10.1021/acs.jproteome.8b00847
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Metabolomics Analysis Identifies the Liver as a Major Organ of Metabolic Disorders in Amyloid Precursor Protein/Presenilin 1 Mice of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is regarded as a metabolic disorder, and more attention has been paid to brain metabolism. However, AD may also affect metabolism in the peripheral organs beyond the brain. In this study, therefore, we investigated metabolic changes in the liver, kidney, and heart of amyloid precursor protein/presenilin 1 (APP/PS1) mice at 1, 5, and 10 months of age by using 1H NMR-based metabolomics and chemometrics. Metabolomic results reveal that the liver was the earliest affected organ in APP/PS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…1). In addition, recent tissue-specific metabolomic analysis revealed that the liver was the earliest affected organ in A␤PP/PS1 mice during amyloid pathology progression [14]. Genetic variants affecting A␤PP and A␤ processing are associated not only with early-onset autosomal dominant AD but also with LOAD [15].…”
Section: Productionmentioning
confidence: 99%
“…1). In addition, recent tissue-specific metabolomic analysis revealed that the liver was the earliest affected organ in A␤PP/PS1 mice during amyloid pathology progression [14]. Genetic variants affecting A␤PP and A␤ processing are associated not only with early-onset autosomal dominant AD but also with LOAD [15].…”
Section: Productionmentioning
confidence: 99%
“…The EGFR signalling network has been identified as a key player in liver disease [ 39 ]. The precise function of APP is unknown but it is involved in Alzheimer’s disease and also has been hypothesised to be involved in liver metabolism [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known, from AD models in rodents, that AD impairs the function of peripheral organs such as liver, kidney, and small intestine (González-Domínguez et al 2015b ; Pan et al 2019 ). Metabolomic results from APP/PS1 mouse models revealed that the liver was the organ first affected during the progression of amyloid pathology, demonstrating impaired energy metabolism, amino acid metabolism, nucleic acid metabolism, as well as ketone and fatty acid metabolism (Zheng et al 2019 ). In addition the systemic effects of physical exercise have also been well demonstrated (Radak et al 2008 , 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%